Studies on the Thermal Variations of Resistance of PVC-Graphite Thick Film Resistors. (2019) - Billa, Poornaiah; Meihru, Y; Rao, Y Srinivasa
Abstract: The percentage variations of resistance of polymer thick film resistors i.e. PVC-graphite thick film resistors has been studied. Four different compositions of PVC-graphite are used in the preparation of polymer thick film resistors. Among the four different PVC-graphite compositions 90% graphite: 10% PVC thick film resistors shows the least variation with temperature changes. This can be attributed to the high composition of graphite content. The variation will be lowered down with an increase in the loading fraction of graphite in polymer thick film resistors. The percentage variations of resistance of polymer thick film resistors, after stored 70°C for 1000hours, or after 25 cycle thermal shock tests as well as the variations after the short term over load tests have also been measured and studied. The variations are still smaller in 90%graphite: 10% PVC polymer thick film resistors. A possible explanation on this smaller variation in 90% graphite: 10 % PVC polymer thick film resistors is also presented.